Epidemiological characteristics and clinical course of eyelid squamous cell carcinoma patients from a large tertiary centre between 2009 and 2020. Issue 8 (12th March 2021) - Klingenstein, Annemarie; Samel, Christina; Messmer, Elisabeth M; Garip-Kuebler, Aylin; Priglinger, Siegfried G; Hintschich, Christoph R
Abstract : Background/aims: To assess epidemiological tumour features, risk factors, clinical management and outcome of eyelid squamous cell carcinoma (SCC) and changes thereof. Furthermore, we searched for validating predictors of the American Joint Committee on Cancer (AJCC) 8 classification system. Methods: We evaluated data of 117 patients with histologically proven eyelid SCC at a large tertiary German university centre between January 2009 and March 2020. This retrospective, monocentric analysis included descriptive statistics and non-parametric tests (p<0.05). Results: Histologically controlled excision and follow-up was performed in 88 (75.2%) patients. In the remaining patients with higher T-category, individual adjuvant therapy combinations were initiated. We found higher numbers of nodal metastasis and recurrence for male patients and higher T-category (p=0.035, p=0.008 and p=0.001, p<0.001). Recurrence rates proved higher for patients with multiple lesions (p=0.008). Disease-specific survival (DSS) was 95.7% at 2 and 94.9% at 5 years of follow-up. Six patients (5.1%) died from eyelid SCC with nodal metastasis and higher T-category being negative prognostic factors (p<0.001 and p=0.009). Mortality was associated with tumour location in the medial upper eyelid, nodal metastasis being more frequent (p=0.001 and p=0.009) and tumour of the lower eyelid alone as positive predictor (p=0.012). T category differed in 34 (29.1%) patients when comparing AJCC 7 and 8 (p<0.001). Changes in T category as per the AJCC 8 classification resulted in better prediction of DSS (p=0.024). Conclusion: Special attention should be paid to male patients, tumour location in the upper medial eyelid and lymph node diagnostics. Prediction of DSS proved superior as per the AJCC 8 staging system.